A Persistent Kuroshio in the Glacial East China Sea and Implications for Coral Paleobiogeography. Issue 7 (7th July 2020) - Vogt‐Vincent, N. S.; Mitarai, S.
Abstract: The Kuroshio Current is a major hydrographical feature of the modern East China Sea, but it has been suggested that its flow was diverted to the east of the Ryukyu Arc at the Last Glacial Maximum. Shoaling of the Yonaguni Depression has also been proposed as a cause of Kuroshio Current diversion which, while unlikely to have been significant at the Last Glacial Maximum, may have been an important consideration further back in time. Using an ensemble of high‐resolution ocean simulations with climatic boundary conditions emulating those of the Last Glacial Maximum, we present the first regional state estimates of the glacial East China Sea which are both physically consistent and compatible with sea surface temperature proxy compilations. We find that while the Kuroshio Current transport in the East China Sea is slightly reduced at the Last Glacial Maximum, its path is relatively unchanged, with limited sensitivity to glacioeustatic sea level change, glacial‐interglacial changes in climate, and tectonic shoaling of the Yonaguni Depression. Simulations with the best model‐proxy agreement predict only limited contraction of the reef front at the Last Glacial Maximum, and strong surface currents associated with the glacial Kuroshio may have maintained or even improved long‐distance coral larval dispersal along the Ryukyu Arc, suggesting that conditions may have enabled coral reefs in this region to remain widespread throughout the last glacial. Further field studies investigating whether this is genuinely the case will provide insights into how the coral reef front responds to long‐term environmental change. Plain Language Summary: Due to their location at the latitudinal limit of the coral reef habitable range (the "coral reef front"), the reefs of the Ryukyu Arc, Japan are particularly useful for understanding the response of reef fronts to environmental change. Reconstructing how this reef front responded to past climate change may allow us to predict how it will change in the future. However, this requires a good understanding of how regional ocean temperatures changed in the past. Ocean temperatures in this region are strongly influenced by a warm current called the Kuroshio Current. Previously, it was suggested that lower sea level in the past changed the path of the Kuroshio. However, by using sophisticated ocean circulation models and comparisons with geological estimates of past ocean temperatures, we have shown that the presence of the Kuroshio Current in the East China Sea is robust to environmental and geological change. Our simulations suggest that the coral reef front in the Ryukyu Arc may not have contracted much during a past cold period and also may indicate that the reef front follows sea surface temperatures in response to long‐term climate change. Additionally, the continued presence of the Kuroshio Current in the past may have maintained (and possibly improved) a steady supply of coral larvae to coral reefs under considerable environmental stress at the coral reef front, improving their resilience. Key Points: We present the first realistic and proxy‐consistent paleoceanography model for the East China Sea at the Last Glacial Maximum The Kuroshio Current remains in the East China Sea through glacial‐interglacial changes in sea level, climate, and tectonics This may explain the limited retreat of the glacial coral reef front by maintaining warm temperatures and facilitating larval transport